Research of Modeling and Motion Simulation of Globoidal Indexing Cam based on Transformation of Homogeneous Coordinate - Zhao Shitian; Fu Yingying; Zeng Yong; Zheng Lei; Zhou Bo (Jixie chuandong)
Aiming at the globoidal indexing cam mechanism,through the theoretical analysis of conjugate surface theory and the differential geometry,the construction method of the universal surface equation of globoidal indexing cam is presented based on transformation of homogeneous coordinate. Then the software of surface points collection system of the globoidal indexing cam is developed based on VB. The 3 D modeling and motion simulation of the globoidal indexing cam mechanism are set up in Pro/E. The mechanism design and motion simulation verification example shows that the designed globoidal indexing cam mechanism satisfied the indexing expectation.